2008
DOI: 10.1088/0953-8984/20/12/125204
|View full text |Cite
|
Sign up to set email alerts
|

On the electronic configuration in Pu: spectroscopy and theory

Abstract: Photoelectron spectroscopy, synchrotron-radiation-based x-ray absorption, electron energy loss spectroscopy, and density-functional calculations within the mixed-level and magnetic models, together with canonical band theory, have been used to study the electron configuration in Pu. These methods suggest a 5f n occupation for Pu of 5 n < 6, with n = 6, contrary to what has recently been suggested in several publications. We show that the n = 6 picture is inconsistent with the usual interpretation of photoemiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
52
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 67 publications
6
52
1
Order By: Relevance
“…The later has the largest occupation number in all considered structures (see the tables below). The large number of f electrons (close to 6) obtained in the present calculation disagrees with previous experimental and theoretical estimations that give 5.1-5.2 electrons [26]. Such a difference between theoretical results originates from dissimiliar band structure calculation methods.…”
Section: Interstitial Plutonium Atom In a 32 Atom Supercellcontrasting
confidence: 82%
“…The later has the largest occupation number in all considered structures (see the tables below). The large number of f electrons (close to 6) obtained in the present calculation disagrees with previous experimental and theoretical estimations that give 5.1-5.2 electrons [26]. Such a difference between theoretical results originates from dissimiliar band structure calculation methods.…”
Section: Interstitial Plutonium Atom In a 32 Atom Supercellcontrasting
confidence: 82%
“…For example, elemental Pu is thought to have an f-orbital occupancy near 5, close to that expected for a 5f 5 ground-state configuration (Pu 3þ ) based on photoemission, N 4;5 -edge X-ray absorption, and electron-energy loss spectroscopy (4,5). In addition to these examples, several researchers have shown that so-called "two-fluid" or "dual nature" models of the 5f orbitals, whereby some fraction of the f-electrons contribute to delocalized behavior and the rest contribute to the more localized local moment behavior, can successfully describe some properties (6) such as coexistent antiferromagnetism and superconductivity in CeRhIn 5 (7), the inelastic neutron scattering of UPd 2 Al 3 (8), de Haas-van Alphen frequencies of UPt 3 (9), and the photoemission spectra of PuCoGa 5 and PuIn 3 (10).…”
mentioning
confidence: 84%
“…Further affirmation is given by a canonical band model with itinerant f electrons, which shows that precisely AmIV is favored over other plausible phases for f occupations corresponding to Am. 32 Another hint that full delocalization has occurred for AmIV is the fact that the magnetic moments are all suppressed at this pressure in the calculations. Any remaining 5f -localization in Am would have manifested itself through spin polarization in the DFT treatment as a necessary but not sufficient condition.…”
mentioning
confidence: 94%